Progress and Hurdles of Therapeutic Nanosystems against Cancer - Marina Martín-Contreras; Saúl A. Navarro-Marchal; José Manuel Peula-García; Ana Belén Jódar-Reyes (MDPI AG, 2022)
Nanomedicine against cancer, including diagnosis, prevention and treatment, has increased expectations for the solution of many biomedical challenges in the fight against this disease. In recent decades, an exhaustive design of nanosystems with high specificity, sensitivity and selectivity has been achieved due to a rigorous control over their physicochemical properties and an understanding of the nano-bio interface. However, despite the considerable progress that has been reached in this field, there are still different hurdles that limit the clinical application of these nanosystems, which, along with their possible solutions, have been reviewed in this work. Specifically, physiological processes as biological barriers and protein corona formation related to the administration routes, designing strategies to overcome these obstacles, promising new multifunctional nanotherapeutics, and recent clinical trials are presented in this review.